The Role of Community Development Programmes in Poverty Aleviation in Nigeria: Lessons from Onelga, Rivers State, Nigeria - Ambrose, Agwu Ositadimma; Etim, Iton Enobong; Mgbe, Enagu, Francis (American Journal of Social Sciences and Humanities, 2016)
This study focuses on the role of community development programmes in poverty alleviation in ONELGA, Rivers State. The study was induced by the level of poverty prevalence among the rural dwellers in ONELGA community despite the abundance of natural resources, complimented by the efforts made by the government to improve the living condition of the people in the rural areas. It was geared toward finding out whether implementation of community based projects in the area has had any significant improvement in the lives and standard of living of people in ONELGA. Data collected from this survey research was from two strata using stratified method where 500 respondents were selected through multistage and snowball sampling method. The questionnaire was also used and administered; the data collected was analyzed through simple percentage and represented in charts. The study found that effective implementation of community based programmes has capacity to impact positively on the lives of ONELGA people. It was then recommended that government should embark on more community development programmes to reduce the level of poverty in the rural areas and to help in funding and completion of community development projects to improve the living conditions of the rural people in ONELGA.